Effect of biorejuvenator types on microstructure, mechanistic performance, and resilient modulus prediction model of asphalt concrete containing recycled materials in Indonesia - Atmy Verani Rouly Sihombing; Bambang Sugeng Subagio; Eri Susanto Hariyadi; Agah Muhammad Mulyadi; Retno Utami; Reza Phalevi Sihombing (Journal of King Saud University: Engineering Sciences, 2024)
Biorejuvenators are rejuvenating agents produced from sustainable biological raw materials. In this study, a biorejuvenator was used in recycled materials, such as reclaimed asphalt pavement (RAP), to determine its effect on the asphalt binder film thickness (ABFT) and resilient modulus (Smix) of an asphalt concrete wearing course (ACWC) mixture, which was tested at the optimum binder content (OBC). The ABFT was investigated using scanning electron microscopy and the Smix was determined from the asphalt mixture test using UMATTA at test temperatures of 20–40 °C. The asphalt mixture was prepared with RAP (0–30%), pen 60/70, aggregates, and two types of biorejuvenators, namely coconut shell bioasphalt (BioCS) and BitutechRAP (from trees). Furthermore, an Smix model was developed for each mixture type. The ABFT value obtained from the microstructural test results for each mixture corresponded with the minimum ABFT requirements for the adhesion criteria of the asphalt mixture, microstructurally demonstrating that the biorejuvenators worked well to restore the performance of 30%RAP in the ACWC mixture. Both types of biorejuvenators could activate the bitumen of the RAP (RA binder) because they could still produce Smix. The value of Smix produced from the RAP and BioCS mixture was greater than that produced from the RAP and BitutechRAP mixture. In the resulting Smix model, the influential volumetric parameters for ACWC + RAP + BioCS and ACWC + RAP + BitutechRAP were the voids in mineral aggregate and voids in asphalt, respectively. Based on the results of the microstructural, mechanistic, and Smix models, BioCS, as a local Indonesian biorejuvenator, has significant potential to rejuvenate recycled materials up to 30%.